The Effect of Leadership Style and Employment Policy on Employee Productivity: A Case Study - Effendy, D. Andry; Santiago, Faisal (Interdisciplinary Social Studies, 2022)
Background: Each individual has their own leadership style in managing and determining their employment policies which affect employee productivity. Aim: This study aims to determine the effect of leadership style and employment policy on employee productivity. Method: This study uses quantitative research methods while data collection techniques are carried out through questionnaires with a sample of 30 as respondents who were selected using random sampling techniques and analyzed using multiple linear regression. Findings: The results showed that the leadership style and employment policy had a significant effect on the productivity of  Syntax Corporation Indonesia employees. The results of the t test analysis obtained a leadership style t significance value of 0.003 and the employment policy t significance value of 0.002 was smaller than 0.5 so that it was proven that the leadership style variable (X1) and the employment policy variable (X2) had a significant effect on employee productivity (Y).